Análisis de la gestión documental del registro de la propiedad del Gobierno Autónomo Descentralizado Municipal del cantón Babahoyo - Contreras Maridueña, Richard Alexis (2021)
The Decentralized Autonomous Government of the Babahoyo canton is a public institution that implements plans, programs, develops social investment works and implements policies with the aim of seeking the well-being of the citizens, where the offer of public services must be characterized with an attention of quality and efficient. The research was carried out in the Property and Commercial Registry Unit in order to analyze document management and its influence on the labor productivity of human talent during the development of work activities related to property registration. The methodology is composed of deductive and inductive methods, while the types of applied research are field and bibliographic; The techniques used are interview and survey, which were aimed at the human talent of the institutional agency studied and citizens of the locality who regularly attend the mediations of the GADM of the Babahoyo canton. The results obtained are: document management does not have an efficient system that allows the automation of internal processes, the user service process is not timely, it takes 5 to 6 days to approve the property certificates, there were inconsistencies in the registry of cadastral codes, coordinates and information plans, while the Quipux national document management system is not used due to difficulties in handling or problems updating the program.